Reduced antioxidant capacity and increased subclinical inflammation markers in prepubescent obese children and their relationship with nutritional markers and metabolic parameters. (1st November 2016) - Vehapoglu, Aysel; Turkmen, Serdar; Goknar, Nilufer; Özer, Ömer Faruk
Abstract : Objective : There are associations between some inflammatory and oxidative markers and obesity in adults, but whether prepubescent children of different weights also have such markers has not been studied. We investigated multiple inflammatory markers and levels of erythrocyte oxidant/antioxidant enzymes in prepubescent children of different weights. Methods : Children aged 2–11 years were divided into three groups: 80 were underweight, 90 were obese but otherwise healthy, and 80 were healthy age- and sex-matched children of normal-weight. We analyzed inflammatory markers and the total oxidant status, total antioxidant status (TAS), and total thiol level were also determined, and the oxidative stress index was calculated as an indicator of the degree of oxidative stress. Results : The obese group exhibited higher levels of fasting glucose, insulin, total cholesterol, triglycerides, the homeostatic model assessment of insulin resistance (HOMA-IR), and the homeostatic model assessment of β -cell function (HOMA- β ), C-reactive protein (CRP), neutrophils, and neutrophil/lymphocyte ratio (NLR), as well as lower TAS and total thiol levels than the other two groups (all P  < 0.001). Moreover, TAS and total thiols were negatively correlated with age in the obese group ( r  = −0.212, P  = 0.001; r  = −0.231, P  < 0.001, respectively). CRP levels in plasma were positively correlated with the body mass index (BMI), insulin and glucose levels, HOMA-IR, HOMA- β, WBC and neutrophil counts, and the NLR, and were negatively correlated with TAS and total thiol levels in the overall studied population. Discussion : The coexistence of increased obesity-related subclinical inflammation and decreased antioxidant capacity can be observed even in prepubescence, and may eventually increase the risk of long-term vascular damage.